Analysis of Secondary Flows in Centrifugal Impellers - Klaus Brun; Rainer Kurz (International Journal of Rotating Machinery)
Secondary flows are undesirable in centrifugal compressors as they are a direct cause for flow (head) losses, create nonuniform meridional flow profiles, potentially induce flow separation/stall, and contribute to impeller flow slip; that is, secondary flows negatively affect the compressor performance. A model based on the vorticity equation for a rotating system was developed to determine the streamwise vorticity from the normal and binormal vorticity components (which are known from the meridional flow profile). Using the streamwise vorticity results and the small shear-large disturbance flow method, the onset, direction, and magnitude of circulatory secondary flows in a shrouded centrifugal impeller can be predicted. This model is also used to estimate head losses due to secondary flows in a centrifugal flow impeller. The described method can be employed early in the design process to develop impeller flow shapes that intrinsically reduce secondary flows rather than using disruptive elements such as splitter vanes to accomplish this task.